Involvement of Phospholipase C in the Norepinephrine-Induced Hypertrophic Response in Cardiomyocytes: Phospholipase C in Cardiac Hypertrophy - Tappia, Paramjit S; Elimban, Vijayan; Dhalla, Naranjan S (Scripta Medica, 2022)
Norepinephrine (NE) is known to mediate cardiomyocyte hypertrophy through the G protein coupled α1-adrenoceptor (α1-AR) and the activation of the phosphoinositide-specific phospholipase C (PLC). Since the by-products of PLC activity are important downstream signal transducers for cardiac hypertrophy, the roleof and the regulatory mechanisms involved in the activation of PLC isozymes in cardiac hypertrophy are highlighted in this review. The discussion is focused to underscore PLC in different experimental models of cardiac hypertrophy, as well as in isolated adult and neonatal cardiomyocytes treated with NE. Particularemphasis is laid concerning the α1-AR-PLC-mediated hypertrophic signalling pathway. From the information provided, it is evident that the specific activation of PLC isozymes is a primary signalling event in the α1-AR mediated response to NE as well as initiation and progression of cardiac hypertrophy. Furthermore,the possibility of PLC involvement in the perpetuation of cardiac hypertrophy is also described. It is suggested that specific PLC isozymes may serve as viable targets for the prevention of cardiac hypertrophy in patient population at-risk for the development of heart failure.
Keywords: Phospholipase C isozymes; Norepinephrine; α1 -adrenoceptor; Cardiomyocytes; Experimental models of cardiac hypertrophy; Signal transduction